Comparison of patient‐reported acute urinary and sexual toxicity scores in a 6‐ versus 2‐fraction course of high‐dose‐rate prostate brachytherapy monotherapy. Issue 1 (29th August 2017) - Ragab, Omar; Banerjee, Robyn; Park, Sang‐June; Patel, Shyamal; Zhang, Mingle; Wang, Jason; Velez, Maria; Demanes, David Jeffrey; Kamrava, Mitchell
Abstract: Introduction: To identify differences in acute urinary and sexual toxicity between a 6‐fraction and 2‐fraction high‐dose‐rate brachytherapy monotherapy regimen and correlate dosimetric constraints to short‐term toxicity. Methods: A single institution retrospective study of 116 men with prostate cancer treated with HDR monotherapy from 2010 to 2015 was conducted. Eighty‐one men had 7.25 Gy × 6‐fractions and 35 men had 13.5 Gy × 2‐fractions. Patients had two CT‐planned implants spaced 1–2 weeks apart. Patient baseline characteristics, International Prostate Symptom Scores (IPSS) and Sexual Health Inventory for Men (SHIM) scores were collected pre‐treatment and 3, 6 and 12 months post‐implantation. Mixed effect modelling was undertaken to compare baseline, 1–6 month and 7–12 month scores between groups. Poisson regression analysis was performed to correlate dosimetric constraints with acute toxicity. Results: There was no difference between baseline and post‐implantation IPSS scores between 6‐fraction and 2‐fraction groups. SHIM scores for men treated with 6‐fractions had a steeper decline at 1–6 months, but resolved at 7–12 months. Pre‐treatment alpha‐blocker use correlated with worse short‐term acute urinary toxicity. Worsened SHIM score correlated with increasing age, diabetes mellitus and androgen‐deprivation therapy. In a dosimetric analysis of outcomes, prostate V150 dose and bladder wall (D01.cc, D1cc, D2cc) dose correlated with increased IPSS score. Conclusion: No increased acute genitourinary or sexual dysfunction has been observed in men when transitioning from 6‐fraction to 2‐fraction HDR monotherapy. A dosimetric correlation was found between the V150 and bladder wall doses for acute urinary toxicity. Future research should continue to standardize and validate dose constraints for prostate HDR monotherapy patients.